A Proposal of Parallelization of Local Search Procedures Applied to the Minimum Cost Hop-and-Root Constrained Forest Problem - Pereira, D. L.; Cunha, A. S.; Meira Jr., W. (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2010: Anais do XI Simpósio em Sistemas Computacionais de Alto Desempenho, 2010)
In this work, we present two parallel heuristics that coordinate the application of many local search procedures to the Minimum Cost Hop-and-root Constrained Forest Problem (MCHCFP), a Combinatorial Optimization problem in which the minimization of the communication costs in a wireless sensor network with constrained delay and number of hops is desired. The coordinated application of local search procedures in parallel must take into account that these search procedures may have different goals, since the MCHCFP requires the minimization of trees and routes. The presented ideas can be generalized to other problems in which a similar situation occurs.